Gallic acid ameliorates thymic involution via activating Sox2 and Nanog - Guo, Li; Cao, Jia‐hui; Cheng, Deng‐wei; Dong, Han; You, Li; Sun, Yun; Ding, Yi; Chai, Yu‐rong (Scandinavian journal of immunology, 2022)
Thymic ageing precedes other organs, which is mainly caused by the gradual loss of thymic epithelial cells, and the thymic epithelial progenitor cells have been found in human and adult mouse. Stem cell transcription factors, sex‐determining region Y‐box2 (Sox2) is strongly involved in organogenesis. Homeobox transcription factor Nanog (Nanog) has been applied in cell reprogramming to generate induced multipotential stem cells for its related pluripotency, and its functions in the thymus remain undefined. Gallic acid, one of the natural products of polyphenols, has been used to counter ageing. In this study, we investigated the alteration of Nanog and Sox2 in the thymus of the natural ageing and D‐galactose‐induced accelerated ageing mice and further explored the effects of gallic acid on their expression. 5‐bromo‐2′‐deoxyuridine (BrdU)‐retaining assay was also performed to trace the thymic progenitor cells. Our study indicated that Nanog and Sox2 showed age‐dependent decrease in the thymus of mice. Nanog, Sox2 and BrdU‐positive cells were also found to be abundant in the area of cortex‐medulla junction (CMJ) of the thymus, which suggested that thymic adult stem cells/progenitor cells may exist in this position. Gallic acid can upregulate the expression of Nanog and Sox2, which suggested it may promote thymus regeneration from age‐related atrophy and D‐galactose‐induced damage by activating the thymic progenitor cells and increasing the expression of Nanog and Sox2.